Do consumers care about the message a claim conveys? The magic bullet effect of organic and domestic claims on food products. Issue 1 (20th September 2017) - Scholl‐Grissemann, Ursula
Abstract: According to the magic bullet effect, as it relates to organic and domestic claims on food products, consumers may attribute inappropriate benefits to a claim. An experimental study reveals 2 such effects, from organic claims to domestic benefits, such that customers attribute domestic benefits to organic claims, and from domestic claims to organic benefits, such that consumers attribute organic benefits to domestic claims. This effect is strengthened by consumers' degree of national identification and ethnocentric beliefs. In line with prior research, the results indicate that consumers pay little attention to the information the claim conveys and instead find what they are looking for by reading into the product claims. These findings have important implications for not only marketing management but also public policies that seek to reduce any confusion created by organic and domestic claims on food products.